2012
DOI: 10.3109/0142159x.2012.668637
|View full text |Cite
|
Sign up to set email alerts
|

Program evaluation models and related theories: AMEE Guide No. 67

Abstract: This Guide reviews theories of science that have influenced the development of common educational evaluation models. Educators can be more confident when choosing an appropriate evaluation model if they first consider the model's theoretical basis against their program's complexity and their own evaluation needs. Reductionism, system theory, and (most recently) complexity theory have inspired the development of models commonly applied in evaluation studies today. This Guide describes experimental and quasi-exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
366
0
25

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 416 publications
(428 citation statements)
references
References 13 publications
1
366
0
25
Order By: Relevance
“…Kirkpatrick's model of programme evaluation [73] is one of the most popular systems for evaluating training programmes [74,75]. A number of studies in the literature reviewed indicated how their authors had evaluated their own programmes according to the four levels of training achievements described by Kirkpatrick [11,14,19,50,63,64,68,76].…”
Section: The Kirkpatrick Classification Of Evaluating Training Programmementioning
confidence: 99%
“…Kirkpatrick's model of programme evaluation [73] is one of the most popular systems for evaluating training programmes [74,75]. A number of studies in the literature reviewed indicated how their authors had evaluated their own programmes according to the four levels of training achievements described by Kirkpatrick [11,14,19,50,63,64,68,76].…”
Section: The Kirkpatrick Classification Of Evaluating Training Programmementioning
confidence: 99%
“…The absence of a control group and the fact that the role-play is considered for evaluation in the discipline may represent a selection bias. Moreover, only the students' satisfaction or reaction and some cognitive or behavioural skills were measured, which places the program evaluation on Kirkpatrick's second-level 10 .After the role-play presentation, the acquired pharmacotherapeutic skills were not assessed, for example, in relation to standardized patients (corresponding to Kirkpatrick's third-level) or in different circumstances in the later stages of the course (corresponding to Kirkpatrick's fourth-level). The impact of the intervention on professional practice could not be evaluated, thus further studies are needed to verify the impact of a long-term intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Entre otros se indican modelos de evaluación convencionales como el de Kirkpatrick (Boud, et al, 2014;Frye y Hemmer, 2012), el modelo de evaluación de los materiales educativos adaptados a las tecnologías como el de Galvis o Cataldi (Cova, Arrieta y Aular de Duran, 2008;Cataldi, Dominighini, Chiarenza y Lage, 2012), o Bostock que propone una Lista de Control para la Evaluación de Software Educativo (Cova, et al, 2008). Y modelos o investigaciones realizadas donde se pone de manifiesto que la evaluación es una herramienta de formación, como las realizadas por Pineda et al (2014aPineda et al ( , 2014b.…”
Section: La Primera Fundamentación Y Antecedentes Corresponden Al Prounclassified